1986
DOI: 10.1111/j.1365-2494.1986.tb01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three clover varieties on growth, 15N uptake and fixation by ryegrass/white clover mixtures at three sites in Wales

Abstract: dry matter accumulation and increased '^N fertilizer uptake, but less nitrogen fixed on the mineral upland site than on the peat soil.Whether ''N was given as ammonium or nitrate made little difference in these experiments.Grass and clover production and nitrogen cycling were compared in 1983 and 1984 at three sites: an upland peaty gley and upland and lowland brown earths. The clover varieties Olwen and SI84 were compared in 1983 and SIOO and S184 in 1984. Ammonium and nitrate sources of '^N were used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…One of the justifications is the belief that some of the nitrogen fixed by the legume would be transferred to the associated crops. It has been reported that the inclusion of legumes in grass pastures often increase grass and protein yield as a result of the nitrogen fixed by the legume to the associated crop especially when they grow together for a long period (Goodman and Collinson;1986). The yield advantages of legume-cereal intercropping system over sole have been reported (Pal et 'al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…One of the justifications is the belief that some of the nitrogen fixed by the legume would be transferred to the associated crops. It has been reported that the inclusion of legumes in grass pastures often increase grass and protein yield as a result of the nitrogen fixed by the legume to the associated crop especially when they grow together for a long period (Goodman and Collinson;1986). The yield advantages of legume-cereal intercropping system over sole have been reported (Pal et 'al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…1977). Fixed more N than S.I84, and companion grass took up more soil N than when growing with S. 184 (Goodman & Collison 1986a). Deeper rooted than S.I84; yield less sensitive to changes in quantity or depth of P than S.184 and S.100 (Goodman & Collison 1986b).…”
Section: Agronomic Performancementioning
confidence: 99%
“…Few studieshave examined thesecloversfordifferences innitrogen(N) fixation and for effects on grass growth and N uptake. In Wales, Goodman & Collison (1986) found that Olwenwhiteclover(medium-largeleaved) produced moredry matter(OM) and fixed moreN than S184 whiteclover(small-medium leaved)undermowing and that the associated grass assimilated more N whengrown with Sl84 than with Olwen.…”
mentioning
confidence: 99%